Peranan Kaunselor Pelajar Di Sekolah Menengah - Nazmi, Md. Noor (1998)
The purpose of this study was to review the administrators, school counselors, and discipline teachers perception of the actual role of the secondary school counselors of the Kerian, Parit Buntar District Education Office. Thirteen administrators, thirteen school counselors and thirteen discipline teachers from 13 secondary schools involved in this study. Questionnaires method based on the Counselor Role Assessment Survey (CRAS) was used to obtained data based on evaluation items for the six aspects of guidance and counseling services provided by the school. Quantitative analysis method was used to analyses the questionnaires. The dependent variable was the school administrators, student counselors and discipline teachers while individual and group counseling services, developmental, educational and career guidance services, assessment and appraisal services, consulting services, coordination and management of a developmental and comprehensive program services and professional ethics, personal growth and development services were independent variables. One Way ANOVA was used to test the difference between variables. The results showed that there were significant differences in perception between the administrators, student counselors and discipline teachers towards the actual role of student counselors in implementing the guidance and counseling services to students in secondary schools in the District of Kerian. Anyway there is no significant differences in perception between the administrators, student counselors and discipline teachers towards the individual and group counseling services being given by the student counselors in secondary schools in the District of Kerian.